Residency and movement patterns of adult Port Jackson sharks (Heterodontus portusjacksoni) at a breeding aggregation site. Issue 4 (10th August 2021) - Bass, Nathan Charles; Day, Joanna; Guttridge, Tristan L.; Mourier, Johann; Knott, Nathan A.; Vila Pouca, Catarina; Brown, Culum
ABSTRACT: Examining the movement ecology of mesopredators is fundamental to developing an understanding of their biology, ecology and behaviour, as well as the communities and ecosystems they influence. The limited research on the residency and movements of benthic marine mesopredators has primarily used visual tags, which do not allow for the efficient and accurate monitoring of individual space use. In this study, the authors investigated the residency and movement patterns of Port Jackson sharks Heterodontus portusjacksoni (Meyer 1793) at a breeding aggregation site in Jervis Bay, south‐eastern Australia, using passive acoustic telemetry to further our understanding of the movement ecology of these important mesopredators. Between 2012 and 2014, individuals were tagged with acoustic transmitters, and their residency and movements within the bay were monitored for up to 4 years. H. portusjacksoni showed strong preferences for particular reefs within and between breeding seasons. Males had significantly higher residency indices at their favoured sites relative to females, suggesting that males may be engaging in territorial behaviour. Conversely, female H. portusjacksoni exhibited higher roaming indices relative to males indicating that females may move between sites to assess males. Finally, H. portusjacksoni showed temporal variation in movements between reefs with individuals typically visiting more reefs at night relative to the day, dusk and dawn corresponding with their nocturnal habits.